Knowledge sharing imperatives on STEM career path intentions among secondary school students in Northern-Central Nigeria (2020)
The study investigates knowledge sharing as a predictor of STEM career path choice intentions among secondary school girls in North- Central Nigeria. The study adopted survey research design. The population comprised 5,433 junior secondary school girls from Federal Government Colleges in the geo-political zone. Multi-stage sampling technique was used to select 361 girls for the study. Instrument for data collection was a validated questionnaire. Data were analyzed using descriptive statistics and binary logistics regression. Findings showed that Knowledge sharing predicted girls STEM career path choice intentions (Cox and Snell R2 = 0.025; Nagelkerke R2 = 0.047, p < 0.05). The study concludes that secondary school students at the junior level have high intentions to choose STEM career path and that the varied indicators of knowledge sharing predicted STEM career path choice intentions of junior secondary school girls in North-Central Nigeria. It was recommended that secondary school authorities should give incentives and or introduce programmes that will motivate and sustain the students’ STEM career intentions such as prizes, awards and recognitions among others for practical projects, quizzes and STEM career debates. Additionally, they should create knowledge sharing opportunities such as playing learning games, group discussions and science clubs for the girls among others.